The Importance of Drama in English Language Teaching for Preparatory School Students - Humairi, Aseel Abbas Khudhair (Journal of Innovation in Education and Social Research, 2024)
The drama lessons were, and still are, suffering from obstacles that holding them back from being taught to students in preparatory schools, and this created a gap that began to widen with time and distance students from this great art. In his teaching, I explained the anticipated objectives of the drama. And I talked about the importance of drama in teaching English language and extent of its impact on the students, too. In conclusion, with the proposed solutions and the actions that must be followed to employ drama in reality in teaching students. to expand their language vocabulary to present.